Biology practical activity during pandemic: Study on obstacles and teachers’ strategies in overcoming it - Ramadhayanti Ramadhayanti; Bambang Supriatno; Eni Nuraeni (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
Practical activity is an integral part of science learning process, including biology. However, during distance learning in the era of COVID-19 pandemic, biology practical activities are often not carried out due to a number of obstacles. This study aims to explain the various obstacles or problems experienced by teachers when conducting biology practical activities during the COVID-19 pandemic. The data of this study were collected by distributing questionnaires to 54 teachers who teach natural sciences in Junior High Schools and biology in Senior High Schools in West Java Province with different lengths of teaching experience. The results showed that the teachers experienced several problems, such as limited allocation of learning time during distance learning, the difficulty of designing practical activities that could be carried out independently by students at home, and the difficulty of finding alternative tools and materials at students' homes. To overcome these obstacles, the teachers has made various efforts and the most chosen were asking students to watch videos of practical activities or simplifying the practical activities so that they can be carried out independently by students at home.Abstrak Kegiatan praktikum adalah bagian tak terpisahkan dari proses pembelajaran sains, termasuk biologi. Namun selama Pembelajaran Jarak Jauh (PJJ) di era pandemi COVID-19, kegiatan praktikum biologi seringkali tidak dilaksanakan karena adanya sejumlah kendala. Penelitian ini bertujuan untuk mengungkap berbagai kendala atau permasalahan yang dialami oleh para guru saat melaksanakan kegiatan praktikum biologi selama pandemi COVID-19. Pengumpulan data penelitian dilakukan dengan membagikan kuesioner kepada 54 orang guru yang mengajar IPA Terpadu di SMP dan biologi di SMA di Provinsi Jawa Barat dengan lama pengalaman mengajar yang berbeda-beda. Hasil penelitian menunjukkan bahwa para guru mengalami kendala berupa keterbatasan alokasi waktu pembelajaran yang tersedia selama PJJ, sulitnya merancang kegiatan praktikum yang dapat dikerjakan secara mandiri oleh peserta didik di rumah, dan sulitnya menemukan alat dan bahan praktikum alternatif yang mudah ditemukan di lingkungan sekitar rumah peserta didik. Untuk mengatasi kendala-kendala tersebut, para guru telah melakukan beragam upaya dan upaya yang paling sering dilakukan adalah meminta peserta didik untuk menonton video kegiatan praktikum dan menyederhanakan kegiatan praktikum agar dapat dilaksanakan secara individu di rumah masing-masing peserta didik.